FOLLICULAR DEVELOPMENT IN POST-PARTUM ANOESTRUS BUFFALOES - KUMAR2, PRAVEEN; BRAMHAIAH K, VEERA; RAO M, MUTHA; GANGARAJU, G (The Indian Journal of Animal Reproduction, 2020)
Pattern of ovarian follicle development and regression was studied in 14 Postpartum Anestrus Buffaloes having >60 days postpartum period. The mean follicles number on both the ovaries was 1.82 ± 0.12 with overall maximum diameter of 7.50 ± 0.33 mm and the same was 8.07 + 0.48 and 6.97 + 0.45 mm on right and left ovaries, respectively. During this Postpartum Anestrus the period follicular development either stopped or undergone atresia without reaching dominance and ovulation. The mean growth rate of follicles was 0.46 + 0.22 and 0.20 + 0.21 mm per day on right and left ovaries, respectively with overall growth rate of 0.55 + 0.13 mm per day, while the mean atresia rate was -0.06 + 0.35 and -0.80 + 0.17 mm per day on right and left ovaries, respectively with an overall atresia rate of -0.75 + 0.11 mm per day. The correlation co-efficient of follicle diameter with follicle growth rate was positively insignificant (P>0.05) while the same with follicle atresia rate was negatively insignificant (P>0.05).